Teknik Pengajaran: Inside Outside Circle dalam Kemampuan Menulis Siswa pada Sekolah SMA di Tangerang - Yanah Mulyanah, Euis (JET (Journal of English Teaching), 2021)
This research is aimed to find out the effect of the inside outside circle on tenth-grade students' writing narrative text at SMAN 3 Kabupaten Tangerang in the academic year 2019/2020. This research used a quasi-experiment with pre-test and post-test design. The technique of teaching used in this research is the inside outside circle. The population is 416 students at the school, and the sample was purposively selected by taking two classes of the tenth grade, each consists of 30 students The data was analyzed by using a T-test at the level significance (α=0.05) and degree of freedom is 58. The result showed that the t-count was higher than the t-table (4.49 > 2.00). In other words, the null hypothesis (H0) is rejected and the hypothesis alternative (Ha) is accepted. It means that the inside outside circle technique can improve the students' writing narrative score and the students will be easier to write because it can improve students' ideas. So, the inside outside circle is recommended to be applied for teaching writing.